A total systems study on Company Q - Baroro, Geb Roj; Carlos, Christine Ann; Catungal, Jan Aimee; Magadia, Aleli Abegail
Company Q is one of the Philippines' pioneering companies in self-service laundry. This industry has so much potential for growth and expansion as it is unconventional in the country and is getting more known in the market. Company Q aims to provide quality laundry services to its customers and make it a lot more affordable and convenient for everyone as compared to the laundry services already known to Filipinos. Self-service laundry allows the customer to bring his own laundry to Company Q branches to wash and dry it by himself using the available technologically advanced automated washing and drying machines. Customers pay for each load and would only have to do the loading and unloading of their clothes in and out of the machines. After which, they have to wait for the cycles to finish. This is how self-service laundry appeals to Filipinos who would want more time to allocate for more important activities. Because Company Q is a relatively young company, it has yet to set standards for its everyday operations hindering it to perform in its optimal level. Currently, it is facing challenges such as keeping records and documenting important elements of the company such as repair and maintenance reports history, customer concerns and operational problems, among others. However,the company is also faring well in the industry - there is high demand for the service, there is positive response from the customers, and the company is looking forward to expanding extensively in various areas of the National Capital Region to cater to a larger market. The group aims to address major problems and concerns by recommending solutions that can minimize its occurrences and costs incurred by the company. Another objective of the study is to prevent replication of these problems in branches that will soon start operations. One of these mentioned problems is the handling of customers who come to the branches in a seasonal trend, with peak periods during weekends and lean periods during weekdays. The reason behind this is that during weekends, people have more time to spend in doing laundry since they have a break from weekday obligations such as work and school. People who prefer to do their laundry at during the weekdays are mostly those who only stay at home such as housewives and house helpers. Greatly varying demand levels pose two concerns to the company: crowd handling and very long queues during peak periods, and idle times and low machine utilization during lean periods. It was observed that machine downtimes are contributors to these long queues during peak periods causing additional inconvenience to the customers, and sometimes even leading to balking. From the interview conducted by the project proponents with the customers, almost 20% of the total of 96 interviewees (see Appendix E) from the 4 branches choose to avail laundry service from another company because of very long queues and intolerable waiting times, the reason being easily manifested by the increasing number of unusable machines in branches such as P. Nova!. This is projected to increase even more since no further preventive actions are taken to solve machine breakdowns. These breakdowns also resulted to earlier cut-off times (cut-off times are set by the company 1.5 hours earlier than closing time to allot enough time for washing and drying before the branch actually closes, however there have been occurrences of cut-off times moved to 3 hours before closing time in order to accommodate the very long queue of people that are yet to be served until the end of branch operating hours. Machines, particularly the dryers, easily break down because it was found out that standard operating procedures for these equipment are not completely followed by the company. These SOPs are clearly stated in the manuals that are packaged with the machines. But because of poor physical layout (e.g. wrong size of exhaust installed, wrong pipe material used) and improper maintenance (e.g. lint containers should be cleaned every after cycle but is not done until a whole day of operation ends), dryer downtimes occur earlier in its useful life. Plans for branch renovations are made but without concrete date of execution. This only exposes the company to even more broken machines translating to opportunity losses. The group then plans to work on establishing the optimal branch layout for the positioning of machines at the same time considering the proper requirements for the HVAC (Heating, Ventilation, and Air Conditioning) System. The number of machines will also be identified per branch to more efficiently allocated resources and not incur unnecessary costs.